As universidades corporativas e sua contribuição para a gestão do conhecimento nas organizações - Vitelli, Ana Paula Dente (2003)
The knowledge society has created new challenges to organizations and their executives once knowledqe and creativity have become main. resources in providing competitive advantage. In this sense, organizations must work on developing new ways of creating value through these intangible resources. Professionals, on the other hand, must continuously invest on their development in order to act as knowledge workers. Corporate universities have been implemented in this context, as a strategic approach to training and development initiatives, along with the realignment of the Human Resource activity, which also assumed a strategic importance. The objective of this research is to understand what corporate universities are and how they work in Brazil, analyzing their contribution to knowledge management processes in organizations. It has been found that corporate universities are better understood as an evolution of the training and development initiatives, and do not work so far as institutions that manage organizational knowledge. Calling themselves 'universities', they gain status in the business context, but do not explore the potential that lies behind the concept of an university: the permanet creation of new knowledge. Regardless of that, it should be granted to corporate universities the value of playing an important role in creating awareness of knowledge as a main economic resource to organizations.